STRUKTUR TRANSITIVITAS DALAM TEKS AWIG-AWIG DESA ADAT DENPASAR - I Putu Permana Mahardika (Universitas Warmadewa, 2025)
This paper examines the transitivity system in the Awig-Awig text of the Denpasar Indigenous Village (TAADAD) and how its patterns reflect the text’s communicative function and social role. As a form of customary law that governs social order in communal life, awig-awig presents a compelling subject for linguistic analysis. The study adopts the framework of Systemic Functional Linguistics to explore how ideational meaning is realized through lexicogrammatical choices within the transitivity system, which comprises processes, participants, and circumstances. A qualitative, phenomenological approach is employed. Data were collected through close observation of language use in the awig-awig and analyzed in terms of the processes, participants, and circumstances present in each clause. The analysis reveals a predominance of relational processes, followed by material and existential ones. This suggests that the text emphasizes definitions, roles, and social relationships as a way of legitimizing norms and behaviors. The findings indicate that the transitivity patterns in the text support its primary function: to explain, guide, and reinforce the values upheld by the customary community.